Sensitivity analysis in periodic matrix models: A postscript to Caswell and Trevisan - Lesnoff, Matthieu; Ezanno, P.; Caswell, H. (Elsevier, 2003)
Periodic matrix population models are a useful approach to modelling cyclic variations in demographic rates. Caswell and Trevisan [1] introduced the perturbation analysis (sensitivities and elasticities) of the per-cycle population growth rate for such models. Although powerful, their method can be time-consuming when the dimension of the matrices is large or when cycles are composed of many phases. We present a more efficient method, based on a very simple matrix product. We compared the two methods for matrices of different sizes. We observed a reduction in calculation time on the order of 24% with the new method for a set of 26 within-year Leslie matrices of size 287 x 287. The time saving may become particularly significant when sensitivities are used in Monte Carlo or bootstrap simulations.